Slip Effects on MHD Boundary Layer Flow over a Flat Plate in Casson Ferrofluid - Muhammad Khairul Anuar, Mohamed; Siti Hanani, Mat Yasin; Mohd Zuki, Salleh (Semarak Ilmu Publishing, 2021)
Present study investigated the slip effects on boundary layer flow and heat transfer on a horizontal flat surface immersed in blood-based Casson ferrofluid. The magnetite and cobalt ferrite ferroparticles suspended into Casson fluid represent by human blood to form Casson ferrofluid are numerically analysed. The study began with the transforming the governing equations which in dimensional partial differential equations to non-dimensional ordinary differential equations by using the similarity variable. Resulting similarity equations then solved by Runge-Kutta-Fehlberg (RKF45) method. The characteristics and effects of the slip parameter, the magnetic parameter and the ferroparticles volume fraction for magnetite and cobalt ferrite on the variation of Nusselt number and the skin friction coefficient are analyzed and discussed.